A randomized, double-blind, placebo-controlled trial to assess the bacterial anti-adhesion effects of cranberry extract beverages. Issue 4 (27th February 2015) - Kaspar, Kerrie L.; Howell, Amy B.; Khoo, Christina
Abstract : Consumption of cranberry extract and/or juice beverages provides ex vivo bacterial anti-adhesion activity. Abstract : In this study, we examined the ex vivo urinary anti-adhesion activity of low-calorie cranberry extract beverages in both a pilot study ( n = 10) and a randomized, double-blind, placebo controlled clinical trial ( n = 59). In the pilot study, subjects consumed a cranberry extract beverage (CEB) or a cranberry extract and juice beverage (CEJB), compared to placebo. Both cranberry beverages utilized a standardized cranberry extract powder at a level equivalent to low-calorie cranberry juice cocktail (LCJC) on a PAC content basis. Clean-catch urine samples collected at baseline and post intervention were tested for anti-adhesion activity utilizing a mannose-resistant human red blood cell hemagglutination assay specific for P-fimbriated E. coli . Results from the pilot study indicated that ex vivo anti-adhesion activity for both cranberry treatments were higher ( p < 0.05) than placebo. In the clinical trial, we compared CEJB to LCJC and a placebo beverage. Post-consumption urine from both cranberry treatment groups showed significantly higher ( p < 0.05) anti-adhesion activity compared to placebo. There were no differences observed in anti-adhesion activity between CJEB and LCJC, indicating similar bioactivity. Therefore, acute beverage consumption of cranberry extract and/or juice provides ex vivo anti-adhesion activity, which may help to improve urinary tract health.